2016
DOI: 10.15666/aeer/1401_047075
|View full text |Cite
|
Sign up to set email alerts
|

Histological Biomarkers in Fish as a Tool in Ecological Risk Assessment and Monitoring Programs: A Review

Abstract: Abstract. Water contamination, both in freshwater and marine ecosystems, has been a serious environmental problem all over the world in the last few decades. One of the most common anthropogenic pollutants, which enter the water bodies are metals and metalloids with no biological functions (As, Cd, Hg, Ni and Pb), pesticides and other persistent organic pollutants such as PAHs, PCBs, tributil tins, dioxins, etc. Most of these pollutants tend to accumulate in biota, biomagnify in the food chains and they are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(58 citation statements)
references
References 172 publications
3
53
0
2
Order By: Relevance
“…Exposure of freshwater fish to elevated metal levels in the aquatic environment, and the subsequent disturbance in iono- and osmoregulatory processes, typically results in morphological changes of their branchial apparatus (Fonseca et al 2016; Yancheva et al 2016). Due to the high plasticity of gill tissue, abovementioned physiological mechanisms can induce tissue damage and/or remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of freshwater fish to elevated metal levels in the aquatic environment, and the subsequent disturbance in iono- and osmoregulatory processes, typically results in morphological changes of their branchial apparatus (Fonseca et al 2016; Yancheva et al 2016). Due to the high plasticity of gill tissue, abovementioned physiological mechanisms can induce tissue damage and/or remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Given the species' capacity to acclimatize and adapt to a wide range of salinities -its distribution extends throughout coastal marine and lowland freshwaters of the boreal and temperate northern hemisphere (Bell and Foster, 1994) -it is an ideal model for studies of kidney structure and function. Whilst the kidney has been the target of many physiological studies aimed at understanding the mechanisms of ion transport in various species of marine and freshwater fishes (Yancheva et al, 2016), it has received considerably less attention in sticklebacks. Earlier comparative studies revealed that the renal structures of freshwater sticklebacks are better developed than those from the marine environment (Ogawa, 1968;Wendelaar Bonga, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…In fish as in higher vertebrates, the kidney performs an important function related to electrolyte and water balance and the maintenance of a stable internal environment. Following exposure of fish to toxic agents such pesticides, histological alterations in the fish kidney were found at the level of the tubular epithelium and glomerulus (Yancheva et al, 2016).…”
Section: Introductionmentioning
confidence: 99%